Brain attack!—How good is the early management of subarachnoid haemorrhage in accident and emergency departments?. Issue 3 (1st May 2000) - Thomson, Simon; Ryan, John M; Lyndon, Julia
Abstract : Objectives —The aim of this study was to assess the characteristics and audit the management of patients for whom a diagnosis of subarachnoid haemorrhage was made and who were admitted to a neurosurgical centre from an accident and emergency (A&E) departent. The objective was to use the results to make recommendations for improving care in this group of patients. Methods —Four neurosurgical centres in the South Thames Region provided lists of patients admitted with a diagnosis of subarachnoid haemorrhage during 1997. The medical records and computed tomography of 162 patient episodes from 20 A&E departments were reviewed. The speed of presentation, the provisional diagnosis and the referral patterns were examined. Patient records were audited to investigate what proportion were treated according to established guidelines while in the A&E departments. Results —63.7% of patients presented to A&E within six hours of ictus and 81.1% within three days. Some 49.2% of patients were seen by a doctor within 30 minutes and 74.7% within one hour. Computed tomography was performed on 18.8% within two hours and only 66.3% within six hours of arrival at the A&E department. Eighteen per cent were treated with nimodipine, 26% with intravenous fluids and 32% were given analgesia before leaving the department. Delays occurred in obtaining computed tomography. Conclusions —The management of patients who present to A&E departments with subarachnoid haemorrhage is suboptimal. Improved awareness of the disorder, management by senior A&E staff and clear care pathways could help with management.